The amphibian's spleen as a source of biomarkers for ecotoxicity assessment: Historical review and trends - Tsukada, Elisabete; Rodrigues, Cândido C.; Jacintho, Jaqueline C.; Franco-Belussi, Lilian [UNESP]; Jones-Costa, Monica; Abdalla, Fábio Camargo; Rocha, Thiago Lopes; Salla, Raquel F. (Elsevier, 2023)
Amphibians are very sensitive to many environmental changes, so these animals are considered good bioindicator models for ecotoxicology. Given the importance of the amphibian spleen for hematopoietic and immune responses, this can be a key organ for the evaluation of biomarkers to monitor the health of individuals in nature or in captivity. In this systematic review, we searched databases and summarized the main findings concerning the amphibian spleen as a source of possible biomarkers applied in different scientific fields. The searches resulted in 83 articles published from 1923 to 2022, which applied the use of splenic samples to evaluate the effects of distinct stressors on amphibians. Articles were distributed in more than twenty countries, with USA, Europe, and Brazil, standing out among them. Publications focused mainly on anatomical and histomorphological characterization of the spleen, its physiology, and development. Recently, the use of splenic biomarkers in pathology and ecotoxicology began to grow but many gaps still need to be addressed in herpetological research. About 85 % of the splenic biomarkers showed responses to various stressors, which indicates that the spleen can provide numerous biomarkers to be used in many study fields. The limited amount of information on morphological description and splenic anatomy in amphibians may be a contributing factor to the underestimated use of splenic biomarkers in herpetological research around the world. We hope that this unprecedented review can instigate researchers to refine herpetological experimentation, using the spleen as a versatile and alternative source for biomarkers in ecotoxicology.
Keywords: Conservation; Disease; Ecotoxicology; Pathology; Splenic; Toxic effects